Visual Identity-Based Earthquake Ground Displacement Testing Method - Chen Su; Zhao Sicheng; Dai Zhijun; Li Xiaojun; Zhou Yue (Shock and Vibration)
Ground deformation observation is wildly concerned in the field of earthquake engineering. This paper proposes a high-precision displacement measurement technology based on both computer vision and numerical simulation. During the earthquake, the vision-based testing system collects visual data of the target installed on the location to be observed. The visual data streams can be quantified to the dynamic relative displacement value automatically, by employing mathematical vision algorithms and then by taking the relative displacement as an intermediate quantity, which is brought into the numerical model for iteration. When the test result is close to the simulated one, the absolute ground displacement data could be obtained approximately. A series of experiments have been carried out to suggest that the proposed method presents an innovative and low-cost solution to ground measurement in high accuracy. The method not only realizes the real-time ground deformation observation; moreover, it also provides a wider range of reliable data support to understand deformation mechanism, investigate seismic source information, and recognize the ground motion characteristics.